1992
DOI: 10.1203/00006450-199203000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-α Gene Expression in Late-Gestation Fetal Rat Lung

Abstract: ABSTRACT. Transforming growth factor-a (TGF-a) is a structural homologue of epidermal growth factor and competes for binding on a common transmembrane protein receptor/kinase. Although TGF-a appears to be more important than epidermal growth factor in embryogenesis and mammalian organogenesis, there is little information regarding its expression in developing lung. Accordingly, we measured levels of immunoreactive TGF-a and its gene expression in late-term fetal rat lung during the transition from the canalicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 20 publications
1
13
1
Order By: Relevance
“…It was reported that the expression is decreased by 50% during the transition from the canalicular (E19 -E20) to the saccular (E21) stage in late-term fetal rat lung (Kubiak et al, 1992). This change of expression is consistent with our chronological analysis of TGF␣ mRNA expression by RT-PCR, which revealed that TGF␣ expression decreases in the prenatal saccular stage and rapidly increases after birth.…”
Section: Discussionsupporting
confidence: 79%
“…It was reported that the expression is decreased by 50% during the transition from the canalicular (E19 -E20) to the saccular (E21) stage in late-term fetal rat lung (Kubiak et al, 1992). This change of expression is consistent with our chronological analysis of TGF␣ mRNA expression by RT-PCR, which revealed that TGF␣ expression decreases in the prenatal saccular stage and rapidly increases after birth.…”
Section: Discussionsupporting
confidence: 79%
“…Overexpression of TGF-␣ disrupts lung morphogenesis (30) and surfactant homeostasis (23). Expression of TGF-␣ is decreased during the late stage of fetal lung development (28).…”
Section: Discussionmentioning
confidence: 99%
“…All of these, except HER3, have tyrosine kinase activity. Binding of secreted growth factors, such as the EGF and other EGF-like growth factors, including transforming growth factor (TGF)-a and epiregulin, induces receptor dimerization, resulting in the phosphorylation of tyrosine residues in the kinase domain (15)(16)(17). Activation of the EGFR has been shown to regulate diverse cellular functions, many of which are associated with fibrogenesis, including cell growth, proliferation, differentiation, migration, survival, and transformation (14,18).…”
mentioning
confidence: 99%